Analisis Hubungan Polifarmasi dengan Interaksi Obat Antihipertensi pada Pasien Gagal Ginjal Kronik dengan Hemodialisis di RSUD Sleman Yogyakarta - Febriyani, Ghesa; Padmasari, Siwi (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2024)
Chronic Kidney Disease (CKD) is a condition of kidney damage lasting more than 3 months, resulting in both structural and functional impairment. According to Riskesdas data from 2018, the number of CKD patients aged ≥15 years in Indonesia increased from 0.2% in 2013 to 0.38%. CKD patients undergoing hemodialysis therapy in outpatient settings generally receive more than one type of medication (polypharmacy), which can increase the risk of drug interactions. This study aims to determine the relationship between polypharmacy and the potential for antihypertensive drug interactions in CKD patients undergoing hemodialysis at RSUD Sleman Yogyakarta in 2022. The study used a retrospective observational analytic design with purposive sampling technique, involving 107 outpatient samples who met the inclusion criteria. Drug interactions were analyzed using a website-based tool from drugs.com, and the data were analyzed univariately and bivariately using the chi-square test. The study results showed that the majority of CKD patients undergoing outpatient hemodialysis were aged 45–54 years (34.57%), male (57.00%), had comorbid conditions (86.91%), used single antihypertensive drugs (53.27%), and used less than 5 types of drugs (61.68%). Of the total patients, 57.94% experienced drug interactions, with a moderate severity level (90.37%) and a pharmacodynamic interaction mechanism (73.33%). The conclusion of this study indicates a significant relationship between polypharmacy and the potential for drug interactions (p=0.001).